Korporativni najemodajalci - Šketa, Živa (Teorija in praksa, 2024)
The article presents exploratory research on the existence of corporate landlords, i.e., legal entities that generate income by renting out residential properties in the Ljubljana rental market. Noting the absence of data concerning the volume of apartments leased by corporate entities in Ljubljana, the article gives an overview of the buyers of apartments in seven new buildings in Ljubljana constructed after 2020. Based on data from the Surveying and Mapping Authority of the Republic of Slovenia, the land register, the Slovenian Business Register and information provided by individual companies, it is demonstrated that in the analysed sample some legal entities also appear in Ljubljana that are buying apartments with the intention of renting them out for profit.
Keywords: corporate landlords; korporativni najemodajalci; najemniški trg; Nepremičnine; rental market; rental of residential properties; stanovanjski najem